Analisis dan Perbaikan Proses Bisnis menggunakan Metode Business Process Improvement (BPI) (Studi Kasus Divisi Simpan Pinjam KPRI UB) - Imam Setyo Wibowo; Nanang Yudi Setiawan; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Simpan Pinjam Division of KPRI UB is a division or unit in KPRI UB that has savings and loan as the main service. Simpan Pinjam Division of KPRI UB has loan application as one of the business processes. In operating the business process, Simpan Pinjam Division still has a problem, such as the completion time of the loan application business process that takes a long time to finish or still has not met the expected time target. Therefore, it is necessary to analyze and improve business process to handle the problem and optimize the performance of the loan application business process. This research uses the Business Process Improvement (BPI) method from the organizing for improvement phase, then the understanding the process phase, to the streamlining phase. BPMN or Business Process Model and Notation is used for modelling the process business, and Five Whys Analysis is used for root cause finding. After obatining the current business process model and business process recommendation model, a simulation is performed to idenfity process validity and to determine the results of time analysis comparison using Bizagi Modeler. From the simulation, it is found that every business process is able to run validly and from the time analysis comparison there is an increase in the average completion time of 53%. It can be concluded from the results that the business process that has been improved is more efficient than the current business process in the Simpan Pinjam Division of KPRI UB.